In vivo and In silico Analysis of Antihypertensive Activities of Ficus religiosa Fruit Extract (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Hypertension is one of the major cardiovascular diseases leading to serious health consequences including cardiovascular events such as stroke and even death. These may also include significant damages to the body’s most organs like heart, kidneys and brain. This deadly disease requires proper treatment drugs with lower cost and fewer adverse effects. In this study, Ficus religiosa fruit has been selected as a candidate plant and its fruit extract was used to perform different pharmacological tests in hypertensive rat model. It was observed that the extract decreased the heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) moderately in comparison to deoxycorticosterone acetate (DOCA) in ethanol‑induced hypertensive rats. These effects were similar to that of atenolol, a standard antihypertensive drug. While testing liver function, it was seen that SGOT and SGPT levels were reduced significantly. The creatinine value was decreased to 0.43±0.2 U/L from 2.9±1.3 U/L (induced by DOCA) and 2.6±1.6 U/L (induced by ethanol). While observing cardiovascular parameters, the fruit extract given at dose of 400 mg/kg, lowered total Cholesterol (TC) to 97 mg/dl from 176 mg/dl, low-density lipoprotein (LDL) to 40 mg/dl from 75 mg/dl and Triglycerides (TG) to 61 mg/dl from 118 mg/dl. The increased values were induced by DOCA. In the same test, the high-density lipoprotein (HDL) was increased to 80 mg/dl from 44 mg/dl.  These changes were comparable to those of the standard drug Atenolol. F. religiosa fruit contains different chemical constituents such as isofucosterol, leucopelargonidin, quercetin and beta sitosterol as reported earlier. Molecular docking studies with some of these constituents showed good binding affinity with the targeted protein (receptor) as compared to the standard drugs. Additionally, all the compounds have satisfied Lipinski’s rules and other pharmacokinetic parameters. Moreover, they showed no adverse effects in aquatic and non-aquatic environments. We, thus, conclude that F. religiosa fruit extract could be taken for the discovery of a safe alternative for managing hypertension.Dhaka Univ. J. Pharm. Sci. 23(1): 23-36, 2024 (June)